The prevalence of inhalation allergen in sample of Iraqi allergic asthma patients in Alrusafa-Baghdad (Journal of the College of Basic Education, 2025)
Various types of allergen are found around us this triggers, such as dander animals, pollen, and other. These allergens cause an immune response that influences the lungs and leads to difficulties in breathing. Study the difference between patients with allergic asthma in 10-25 year and 26-41 year age groups rather than patients in (< 42 years) age group. Work included ELISA technique to measure serum level of specific IgE, and aeroallergen type. The present study included 150 patients with allergic asthma, males 66 (44 %) and females 84 (56%), their ages ranged between 10-65 years, who attended the Allergy Specialized Centre in Baghdad, during the period from September 2019 to February 2020. It also, a recorded result of a specific immunoglobulin E (s-IgE) test regarding the type of aeroallergen showed that D. farinae, Alder pollen, and White Oak pollen have obtained the first rank. At the same time, Aspergillus fumigatus, and Cladosporium herbarium take the last rank. The majority of females who were enrolled in this study were more exposed to allergens compared to males his study showed an increased difference between patients with allergic asthma in the 10-25 year and 26-41 year age group rather than patients in (< 42 year) age group. This aeroallergen could be considered a significant element in the pathogenesis of allergic asthma.